2010
DOI: 10.3109/00016349.2010.517307
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of first and second trimester ultrasound screening for fetal anomalies in the southeast region of Sweden

Abstract: The results showed the advantages of the later scan in discovering anomalies of the heart, urinary tract and CNS, and of the early scan in discovering chromosomal aberrations. Lethal malformations were detected at a high level in both groups, but detection of heart malformations needs improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
(36 reference statements)
3
25
2
Order By: Relevance
“…Thirty minutes were allocated for each scan, irrespective of maternal BMI. The details of the scanning procedure and training of the personnel are described elsewhere [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Thirty minutes were allocated for each scan, irrespective of maternal BMI. The details of the scanning procedure and training of the personnel are described elsewhere [16]. …”
Section: Methodsmentioning
confidence: 99%
“…It is possible to detect about 50% or more major malformations at 11-14 weeks of gestation (Rossi 2013). Further on, the majority of potentially lethal malformations like acrania, lethal skeletal dysplasia, megacystis, encephalocele and body stalk anomaly can be detected in the 11-14 week scan (Hildebrand 2010).…”
Section: F U T U R E P E R S P E C T I V E O F C L I N I C a L I M P mentioning
confidence: 96%
“…The study reported that this scan led to the diagnosis of around half of cases of double outlet right ventricle, hypoplastic left heart, and transposition of the great arteries, around onethird of cases of atrioventricular septal defect, coarctation of the aorta, tetralogy of Fallot, and pulmonary atresia, but none of the cases of ventricular septal defect, Ebstein anomaly, aortic or pulmonary stenosis, tricuspid atresia, or cardiac tumors. A recent review of the published series with more than 1,000 cases from 1993 to 2008, which included data from 36,237 pregnancies generated by eight centers, suggests that the overall detection rate of major CHD at 11-13 weeks is 29% (95% CI 25-33) [6] . The pooled detection rate of cardiac defects was 17% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Moreover, the detection of fetal CHD in the first trimester is even lower. A review of the published series with more than 1,000 cases from 1993 to 2008, which included data from 36,237 pregnancies generated by eight centers, suggests that the overall detection rate of major congenital anomalies at 11-13 weeks is 29% [6] . The detection rate of CHD in the first trimester has been estimated at around 30% [7] .…”
Section: Introductionmentioning
confidence: 99%